Circulation in the Seaflower Reserve and Its Potential Impact on Biological Connectivity - Lopera, Luisa; Cardona, Yuley; Zapata-Ramírez, Paula A. (Frontiers in Marine Science, 2020)
The influence of the ocean currents over marine population connectivity is pivotal in territory planning since they should be considered in marine protected areas (MPA’s) design and its implementation, marine spatial planning strategies, restoration plans, among others. Their influence is also vital to broadening the relationship knowledge between oceanographic drivers and ecosystems configuration. However, and despite their importance, knowledge of ocean currents and its role in corals connectivity is poorly know at the Seaflower Marine Reserve, an area that harbours the third large true barrier reef in the world and that was declared as Biosphere Reserve in 2000. To fill-in this gap, here we characterized larvae transport patterns associated to the surface currents that lead connectivity at the Reserve.To achieve this aim, we simulated the advection of buoyant coral larvae of Acropora Palmata, sp during nine spawning events. Larval dispersal patterns were obtained through the offline coupling of a high spatiotemporal resolution hydrodynamic field and a biophysical lagrangian model for particle dispersion. The ocean currents fields were generated through a Regional Ocean Modelling System (ROMS) adequately configured for the domain. Larvae dispersion was carried out throughout an Individual-Based Model (Ichthyop). Results show that there are heterogeneous connectivity patterns during the spawning events at season and inter-annual scales. This behaviour seems to be associated with the high spatiotemporal dynamic variability in the region, such as the Caribbean Current bifurcation close to the Nicaraguan Rise, the intrusion-formation of mesoscale or sub-mesoscale eddies, and the semi-permanent presence of the Panama-Colombia Gyre. We also found that Serranilla, Providencia, Quitasueño and Serrana acts as sinks. In contrast, the northernmost reefs, Serranilla, B.Alicia, and B.Nuevo, seems to be the most important larvae source, highlighting the need of the incorporation of these areas in the current MPA zonification, that could lead to the improvement of the MPA effectiveness. Findings also suggest the possibility to implement an MPA network between Jamaica and Colombia that could allow the populations to be more resilient to environmental changes and less prone to local extinctions.